Muslim community response on impacts of globalization - Ismail Haji Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article looks at the globalization from both, conventional and Islamic perspectives. The concept of globalization, if implemented fairly, is in line with Islamic teaching. Therefore, it is important for the Muslims to examine its response towards globalization. Muslims must be able to identify the strategic issues with regard to globalization and develop concrete measures that are implementable, as well as to be able to differentiate between the positive and negative impact of globalization. More educational and economic cooperation must be established among Muslim countries, and Muslims need to engage in more scientific research in all areas of education, economy, science and technology. The Western scholars have interest in issues in the Muslim world. They look at these issues systemically and methodically, and they seemed to show an inclination towards an open attitude in accepting the relevance of Islam in the modern world. Therefore it is really important to have research cooperation with them.